Analisis Yuridis Terhadap Penyelesaian Konflik Pertanahan Di Areal Tanah Garapan - Kusuma, Juanda; Idham, Idham (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
The problem of land is a very important conflict because it involves the needs of many people's lives to be used as a place to build a house as a place to live, a place of business or as a source of community work. The type of research used in writing this journal is normative juridical research. The point here is a research data based on literature research with legal theory that is specific in the field of land law. Data research is carried out by concluding secondary data which is then carried out with qualitative analysis to review problems based on data and legislation related to the field of land law to obtain a new picture in order to strengthen an existing picture in answering problems which then make conclusions and useful suggestions. . Land problems in Langkat Regency occur because of the lack of awareness and knowledge of the law in the community and poor behavior due to the high linkage of land in meeting the daily needs of the people in Langkat Regency. Resolution of the problems that occur is carried out through mediation at the district land office and if the mediation route fails, generally the problem is continued through litigation (courts).